RESUSITASI KARDIO PULMONER (RKP) SEBAGAI SALAH SATU BEKAL KETERAMPILAN PROFESI GURU PENDIDIKAN JASMANI - Bambang Priyonoadi (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractTeachers of physical education have a major role in handling respiratory problems experienced by any member of the school communitysince they have gained adequate knowledge of physiology and anatomy and skills of giving first-aid treatment, one of which is the skill of providing the basic life support stage of cardiopulmonary resuscitation (CPR).When providing the basic life support stage of CPR, they have to rely on the steps called ABC, short for airway management, breathing, and circulation, referring to respiratory duct release, oxygenation, and artificial circulation, since those steps are standard operations for CPR. Therefore, they have to be able to characterize and identify types of respiratory disturbances and threats and their causes as well as to carry out help techniques in order to handle them.Teachers of physical education are considered skilled in conducting CPR since they have had practice in it. Therefore, amount of practice is a factor which defines the amount of success in providing basic life support.Key words: teacher of physical education, cardiopulmonary resuscitation(CPR)